Effect of Cutting Fluid Supply Strategies on Surface Finish of Turned Parts - Islam, Mohammad Nazrul; Rafai, Noor; Heng, Boon (Trans Tech Publications Ltd., 2011)
This paper presents the experimental and analytical results of different cutting fluid supply strategies—dry, minimum quantity lubrication (MQL) and flood turning in terms of the surface finish of turned parts. Subsequently, the influence of independent input parameters on surface finish is investigated in order to optimize their effects. Three techniques—traditional analysis, Pareto ANOVA analysis, and the Taguchi method—are employed. Initially mild steel AISI 1030 has been selected as the work material. The results indicate that the cutting fluid supply strategy has insignificant influence on the surface finish of turned parts. However, the amount of cutting fluid in MQL showed some influence. Further research on two additional materials, aluminum 6061 and alloy steel AISI 4340, reveals that the surface roughness for different work materials is influenced differently by the cutting fluid supply strategies and there is a scope for optimizing the cutting fluid supply strategy in terms of both method and the amount of cutting fluid. This will reduce the amount of cutting fluids used and consequently, their negative impact on the environment, by avoiding unnecessary applications.